Building resilience to climate change impacts in the Ikel watershed in the Republic of Moldova : a system dynamics approach - Ciobanu, Natalia. (Thesis (Ph.D.) - Bogazici University. Institute of Environmental Sciences, 2022., 2022)
Climate change threatens social-ecological systems (SES) across the globe. Developing countries where agriculture is a major income source for both local communities and the national economy are especially affected. In conjunction with their reliance on climatic resources, these countries face the challenge of data scarcity. Assessing and building the resilience of these communities to climate change impacts is equally important and challenging. As the relationship between science, policy, and practice changes, the demand increases on research to engage productively with stakeholders and ensure positive outcomes for all parties. Efforts are increasingly focusing on building the resilience of SES to climate impacts. In this research, I design, build and implement a client-based process under data scarcity conditions in a network governance setting within Republic of Moldova. The process includes analyzing a complex socio-ecological problem to identify policies helpful in meeting development objectives: improving crop yields, preserving groundwater resources and securing habitats for biodiversity conservation. To this end, I first develop a computer simulation model – Ikel CliRes – using a participatory approach that combines several methods, techniques and tools from two related fields: system dynamics and resilience of socio ecological systems. I then use Ikel CliRes to design policy interventions that increase the desirable resilience of Ikel SES to some climate impacts. Ongoing implementation of several policies discussed with decision-makers is underway pointing to the effectiveness and usefulness of the process. Results should be regarded within the limitations of the model architecture and of the assumptions underlying both the model and the analysis.
Keywords: Climate change mitigation -- Moldova.